PERAN DA'I DESA DALAM MEMBINA MASYARAKAT DESA SEMELAKO 1 DI KABUPATEN LEBONG - Poby Marpelta; Anrial Anrial; Pajrun Kamil (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
This study aimed to find out a depiction of the role of Da'i in Semelako 1 Village, Lebong Regency, Bengkulu, in fostering the community. This study applied a qualitative approach. Data collection techniques were observation and interviews. After the data were collected, the data were further analyzed using Miles's et al approach. This study revealed the following conclusion: First, Da'i activities in delivering da'wah to the people of Semelako 1 Village, Lebong Tengah Sub-district, Lebong Regency, were not going well because the Da'i did not have a plan; the preaching pattern was still monotonous; the materials used were not yet well-organized and very much set according to the wishes of the mad'u / audiences, and the methods used were less varied. Second, the supporting factors of Da'i in efforts to develop religion were the support from the villages government and religious leaders in the form of appeals to participate in Islamic study activities and the provision of facilities and infrastructure such as mosques and prayer rooms. The inhibiting factors extended to the level of the economy classified as underprivileged, and the busy routines of people who worked as farmers every day so that they prioritized fulfilling family needs rather than attending Islamic study activities.